2004
DOI: 10.1111/j.1440-1681.2004.04085.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitroreductase: A Prodrug‐activating Enzyme for Cancer Gene Therapy

Abstract: 1. The prodrug CB1954 (5-(aziridin-1-yl)-2,4-dinitrobenzamide) is activated by Escherichia coli nitroreductase (NTR) to a potent DNA-crosslinking agent. 2. Virus-mediated expression of NTR in tumour cells sensitizes them to CB1954 in vitro and in vivo, providing the basis for a strategy of cancer gene therapy. 3. A phase I trial of CB1954 in cancer patients has been completed, documenting the pharmacokinetics and establishing an acceptable dose. Subsequent trials of the replication-defective adenovirus CTL102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 39 publications
0
80
0
1
Order By: Relevance
“…24 More recently, a replication-defective adenoviral vector CTL102 encoding gene has been used on patients with primary or secondary liver cancer 25 and prostate cancer. 8,26 However, there are many challenges yet to be overcome for it to be considered a robust therapy. For any GDEPT system, there is a need for methods to monitor sufficient incorporation of the transgenes into tumor cells, gauge adequate level of gene expression and predict the duration of transgene expression in cancer Noninvasive optical imaging of NTR GDEPT system S Bhaumik et al cells.…”
Section: Discussionmentioning
confidence: 99%
“…24 More recently, a replication-defective adenoviral vector CTL102 encoding gene has been used on patients with primary or secondary liver cancer 25 and prostate cancer. 8,26 However, there are many challenges yet to be overcome for it to be considered a robust therapy. For any GDEPT system, there is a need for methods to monitor sufficient incorporation of the transgenes into tumor cells, gauge adequate level of gene expression and predict the duration of transgene expression in cancer Noninvasive optical imaging of NTR GDEPT system S Bhaumik et al cells.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] Phase I trials of CB 1954, alone 56 and in conjunction with a non-replicating NTR-armed adenovirus have been conducted. 57,58 However, CB 1954 has poor formulation characteristics 56 that have not been overcome by analog development 59,60 and a limited bystander effect in 3D cell culture models and xenografts. 46,61,62 Of critical importance, CB 1954 provides disappointing plasma concentrations in humans (5.8 mmol h l À1 ) 56 relative to mice (320 mmol h l À1 ) 63 because of dose-limiting hepatotoxicity and diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Anlezark et al (1992) reported that the nitroreductase encoded by the nfsB gene of Escherichia coli could activate CB1954, leading to the initial adoption of this enzyme for use with CB1954 in GDEPT Bridgewater et al, 1995;Grove et al, 1999;Searle et al, 2004). The expression of NfsB in cancer cells using replicationdefective retrovirus or adenovirus vectors was shown to confer greatly increased sensitivity to CB1954, and anti-tumour activity was shown in vivo (McNeish et al, 1998;Djeha et al, 2000Djeha et al, , 2001Weedon et al, 2000).…”
mentioning
confidence: 99%